Paroemias as explication of human qualities in the english language - Azharbekova, E.N.; Mazhitayeva, Sh.; Omasheva, Zh. M.; Toleubaeva, K.; Talaspaeva, Zh.; Zhetpisbay, Sh. (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2020)
The article studies human qualities and cultural features through a zoomorphic cultural code. The authors analyzed English paroemias, which are the most distinctive and culture-specific language system, which contributes to define the native speaker’s worldview features. As a result of the analysis, the authors defined groups of paroemias in which the description of human qualities was found in paroemiological units and figurative content which are related to cultural and national features of the English ethnic group. A component analysis of denotative space of the English paroemias showed that the most relevant for the British are such zoomorphic images as: dog, sheep, cat, horse, ox. The cultural and linguistic specifics, based on paroemias studied, are implicit and serve to create the expressiveness and a figurative meaning and, therefore, are a part of the connotative macro-component. The study, presented here, consulted A. A. Khazan’s English paroemiological dictionary “Russian-English-Latin dictionary of winged words and expressions” (Smolensk: Rusich, 2001), ethnolinguistic and linguocultural scientific works. The target of research is zoonymous proverbs and sayings in the English language. The research focuses on proverbs and sayings zoonyms, in the semantics of which there are cultural and linguistic components characterizing human qualities. The research methods include descriptive, statistic, transformational, distributive and componential analyzes.
Keywords: semantics; English proverbs; English sayings; phraseological unit; lexeme; zoonym; zoomorphic image